Estimation of Multi-Constellation GNSS Observation Stochastic Properties Using a Single-Receiver Single-Satellite Data Validation Method - El-Mowafy, Ahmed (Maney Publishing, 2015)
The single receiver single satellite validation method is a technique that screens data from each satellite independently to detect and identify faulty observations. A new method for estimation of the stochastic properties of multi-constellation GNSS observation is presented utilising parameters of this validation method. Agreement of the characteristics of the validation statistics with theory is used as the criterion to select the best precision of the observations, spectral density and correlation time of the unknowns. A curve fitting approach in an iterative scheme is employed. The method is applicable to any GNSS with any arbitrary number of frequencies. Demonstration of the method results and performance is given using multiple-frequency data from GPS, GLONASS and Galileo in static and kinematic modes.